A New Stem-inhabiting Gall Midge of Poa pratensis (Diptera: Cecidomyiidae). - Barnes, Horace Francis (Contributions to Entomology = Beiträge zur Entomologie, 1958)
A new species of Cecidomyidae belonging to the genus Mayetiola is described as M. schoberi. This species is characterised by the curious hook-shaped terminal sclerotisation of the penis-sheath. Its host plant is Poa pratensis and the type locality Ratzeburg (near Lübeck).Nomenclatural Actsschoberi Barnes, 1958 (Mayetiola), spec. n.